Improving Elderly Patient Care Coordination by Focusing on Outpatient Providers' Needs. Issue 1 (June 2021) - Tremoulet, Patrice; Kurtz, Jon Tyler; Stroka, Ryan
Outpatient providers rely upon discharge summaries to obtain the clinical information about patients recently discharged from acute care settings. This information is needed to coordinate care for those patients, and currently there is a great deal of variability in the content, format, and organization of discharge summaries supplied by acute care providers in the United States. Prior research has identified the information that outpatient providers who care for elderly patients would like to be able to find in discharge summaries, but has not addressed how those providers would like this data to be presented. To gain insight into how to best convey clinical information about recently discharged elderly patients, eleven outpatient physicians participated in interviews and completed a card sorting task.